Improving Employee Performance Effectiveness Strategy In Implementing Hybrid Working At Switching Service Companies - Aprinda Efendi Daulay; Harianto Harianto; Zenal Asikin (Green Publisher Indonesia, 2024)
One of the impacts of the COVID-19 pandemic on industries in Indonesia is the implementation of strict mobility restrictions, including in the IT industry. The increased demand for online services and information technology has driven development and innovation to create new ideas in the application of information technology across various fields, such as e-commerce, online learning, work from home (WFH), and others. This study aims to analyze the factors influencing employee performance and formulate strategies to improve employee performance effectiveness in the implementation of a hybrid work system in switching service companies. The study involves 83 samples using probability sampling techniques with simple random sampling. Data processing employs the Confirmatory Factor Analysis (CFA) method and the Structural Equation Modeling (SEM) method. The results show that Work Environment, Technology Infrastructure, Work Efficiency, and Intrinsic Motivation have a significant direct impact on Employee Performance, and Work Autonomy has a significant indirect impact through the Intrinsic Motivation variable on Employee Performance. However, Work Autonomy does not have a significant direct impact on Employee Performance. Several recommendations include efforts to address issues hindering performance achievement, particularly in cases where employees experience a decline in performance when the hybrid work system is implemented. To enhance employee performance, companies can take strategic steps in several crucial aspects, such as work environment, technology infrastructure, work efficiency, and intrinsic motivation.